2005
DOI: 10.1111/j.1365-2141.2004.05318.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology and management of relapsed acute myeloid leukaemia

Abstract: SummaryDisease relapse remains the major cause of treatment failure in adults with acute myeloid leukaemia (AML). This reflects both the failure of current salvage regimens and the absence of effective strategies to secure long-term disease-free survival in those patients who achieve a second remission. Recent progress in understanding the pathogenesis of relapsed disease has enabled the identification of a variety of dysregulated molecular pathways and these now provide a rational basis for the design of nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 159 publications
2
45
0
Order By: Relevance
“…There is an ongoing need for new and better treatments for patients with advanced disease and poor risk cytogenetics who have an unsatisfactory outcome with any treatment regimen. These risks are often compounded by the cumulative morbidity of multiple reinduction therapies [29] and pre-HSCT infections. Nonetheless we observed continuing freedom from relapse in 66% of such patients, supporting the promise of leukemia control using RI allografts.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing need for new and better treatments for patients with advanced disease and poor risk cytogenetics who have an unsatisfactory outcome with any treatment regimen. These risks are often compounded by the cumulative morbidity of multiple reinduction therapies [29] and pre-HSCT infections. Nonetheless we observed continuing freedom from relapse in 66% of such patients, supporting the promise of leukemia control using RI allografts.…”
Section: Discussionmentioning
confidence: 99%
“…24 Patients in the high-risk group and with time of remission less than 6 months should be referred to clinical trials or better supportive care. [25][26][27] In our cohort, 59 out of 61 patients presented active disease, i.e., patients who had failure in previous treatments, including previous ASCT. Despite that, our population was relatively heterogeneous; the present manuscript reports the experience of a large reference Comprehensive Cancer Center in southern Europe that serves a 3 million habitant area in the North of Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, we have recently shown that a chemo-immunotherapy combining Gemtuzumab Ozogamicin (GO), intermediate dose Ara-C and Mitoxantrone (MIDAM regimen) 7 represents a valid therapeutic option in this setting, allowing to achieve an overall response (OR) rate of 63%, and a disease-free and OS rates of 41 and 53%, respectively, at 2 years. Moreover, we have also shown that normal karyotype (NK) AML patients, receiving the MIDAM protocol and who had a favourable molecular profile (that is, mutated nucleophosmin gene (NPM1 þ ) without internal tandem duplications of the fms-like tyrosine kinase 3 gene (FLT3-ITDÀ)), retained a good prognosis compared with other subgroups with NK.…”
Section: Introductionmentioning
confidence: 99%